PENGARUH PEMAHAMAN GOOD CORPORATE GOVERNANCE, MEKANISME REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN - Firda Eka Khoirun Nisa; Lailatul Amanah (LPPM STIE YKPN Yogyakarta, 2025)
This research aimed to examine Good Corporate Governance understanding and the meachanism of reward and punishment on the employees’ performance at PT Asana Alfa Indonesia Surabaya. The research was quantitative. Furthermore, the population was all employees who worked at PT Asana Alfa Indonesia, in Surabaya. The data collection technique used purposive sampling, in which the sample was based on criteria given. In line with that, 40 employees of PT Asana Alfa Indonesia Surabaya who worked for more than 1 year fulfilled the criteria as the respondents. Moreover, the instrument in the data collection technique was a questionnaire with the 5 Likert scale. The questionnaires were distributed to the respondents. Additionally, the data analysis technique used multiple linear regression with the SPSS (Statistical Product and Service Solution)26. The result showed that Good Corporate Governance understanding and the mechanism of reward and punishment affected the employees’ performance at PT Asana Alfa Indonesia, in Surabaya. In conclusion, the hypothesis was proven.